Implementasi Kurikulum Merdeka di SMP IT Ikhwanul Muslimin II - Arlina, Arlina; As-Shafa, Asri Salwa; Daffa, Mhd. Faiz; Dalimunthe, Nur Fadillah (Lembaga Yasin AlSys, 2025)
This research aims to implement learning aligned with the Kurikulum Merdeka (Independent Curriculum). The Kurikulum Merdeka is a newly launched curriculum by the Ministry of Education, Culture, Research, and Technology (Kemdikbudristek) in response to the learning crisis caused by the COVID-19 pandemic that began in 2019. This study seeks to explain and provide an overview of the implementation of the Kurikulum Merdeka in Sekolah Penggerak (Driving Schools). The research method employed is qualitative, involving interviews and observations. The findings indicate that the implementation of the curriculum in Sekolah Penggerak has been conducted optimally and is ongoing, although there are still several shortcomings and challenges. The key to successful implementation of the curriculum in Sekolah Penggerak lies in the willingness of school principals and teachers to embrace change. The school principal, as a leader, must be able to shift the mindset of the school’s human resources to accept and implement changes, enabling the successful adoption of the Kurikulum Merdeka.